African economic forecasts are brighter - David Mehdi Hamam (Africa Renewal, 2005)
Africa’s economic performance over the last three decades has been mixed, with the 1980s often referred to as a “lost decade,” while the mid-1990s brought the beginnings of a recovery. Since then, growth in sub-Saharan Africa has averaged well above 3 per cent a year, compared with just 1 per cent annually during the first half of the 1990s.